Intercalation Strategy in 2D Materials for Electronics and Optoelectronics. Issue 9 (16th August 2021) - Li, Zexin; Li, Dongyan; Wang, Haoyun; Chen, Ping; Pi, Lejing; Zhou, Xing; Zhai, Tianyou
Abstract: Intercalation is an effective approach to tune the physical and chemical properties of 2D materials due to their abundant van der Waals gaps that can host high‐density intercalated guest matters. This approach has been widely employed to modulate the optical, electrical, and photoelectrical properties of 2D materials for their applications in electronic and optoelectronic devices. Thus it is necessary to review the recent progress of the intercalation strategy in 2D materials and their applications in devices. Herein, various intercalation strategies and the novel properties of the intercalated 2D materials as well as their applications in electronics and optoelectronics are summarized. In the end, the development tendency of this promising approach for 2D materials is also outlined. Abstract : Intercalation strategy for 2D materials has been a current research hotspot due to the strong tunability of chemical and physical properties. This review highlights the recent developments of intercalation methods and applications focusing on electronics and optoelectronics. The remaining challenges and potential applications in the future are also discussed.